COVID-19 and cancer: an extensive review - Mello, Tomás de Souza; Azevedo, Rafael Bellotti; Gonçalves de-Hollanda, João Victor; Ferreira, Leonardo Villa Leão; Montalvão, Fabricio (Brazilian Journal of Oncology, 2021)
Emerging data postulates that cancer is an important risk factor for disease severity and higher in-hospital mortality amongst patients with COVID-19. From a pathophysiological perspective, COVID-19 induces an overproduction of inflammatory cytokines, causing systemic inflammation, hypercoagulability, and multiple organ dysfunction syndrome. The exact pathophysiological mechanisms associated with severe COVID-19 disease in patients with cancer is uncertain. Moreover, the challenge of implementing social distancing in patients requiring specific anticancer treatments urged international societies to issue recommendations regarding the adoption of safety measures to reduce transmission risk and optimize anticancer treatment during the COVID-19 pandemic. We provide an extensive review of the clinical outcomes, prognosis and management of patients with cancer and COVID-19 infection.
Keywords: COVID-19; Cancer; Pathophysiology; Clinical outcome; Management.